Renin-Angiotensin System Pathway Therapeutics Associated With Improved Outcomes in Males Hospitalized With COVID-19*. Issue 9 (18th May 2022) - Rocheleau, Genevieve L. Y.; Lee, Terry; Mohammed, Yassene; Goodlett, David; Burns, Kevin; Cheng, Matthew P.; Tran, Karen; Sweet, David; Marshall, John; Slutsky, Arthur S.; Murthy, Srinivas; Singer, Joel; et al.
Abstract : OBJECTIVES: To determine whether angiotensin receptor blockers (ARBs) or angiotensin-converting enzyme (ACE) inhibitors are associated with improved outcomes in hospitalized patients with COVID-19 according to sex and to report sex-related differences in renin-angiotensin system (RAS) components. DESIGN: Prospective observational cohort study comparing the effects of ARB or ACE inhibitors versus no ARBs or ACE inhibitors in males versus females. Severe acute respiratory syndrome coronavirus 2 downregulates ACE-2, potentially increasing angiotensin II (a pro-inflammatory vasoconstrictor). Sex-based differences in RAS dysregulation may explain sex-based differences in responses to ARBs because the ACE2 gene is on the X chromosome. We recorded baseline characteristics, comorbidities, prehospital ARBs or ACE inhibitor treatment, use of organ support and mortality, and measured RAS components at admission and days 2, 4, 7, and 14 in a subgroup ( n = 46), recorded d -dimer ( n = 967), comparing males with females. SETTING: ARBs CORONA I is a multicenter Canadian observational cohort of patients hospitalized with acute COVID-19. This analysis includes patients admitted to 10 large urban hospitals across the four most populated provinces. PATIENTS: One-thousand six-hundred eighty-six patients with polymerase chain reaction-confirmed COVID-19 (February 2020 to March 2021) for acute COVID-19 illness were included. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Males on ARBs before admission had decreased use of ventilation (adjusted odds ratio [aOR] = 0.52; p = 0.007) and vasopressors (aOR = 0.55; p = 0.011) compared with males not on ARBs or ACE inhibitors. No significant effects were observed in females for these outcomes. The test for interaction was significant for use of ventilation ( p = 0.006) and vasopressors ( p = 0.044) indicating significantly different responses to ARBs according to sex. Males had significantly higher plasma ACE-1 at baseline and angiotensin II at day 7 and 14 than females. CONCLUSIONS: ARBs use was associated with less ventilation and vasopressors in males but not females. Sex-based differences in RAS dysregulation may contribute to sex-based differences in outcomes and responses to ARBs in COVID-19.